Engagement with online self-tests as a predictor of student success. Issue 5 (29th July 2017) - Thomas, Judith A.; Wadsworth, Dan; Jin, Ying; Clarke, Jim; Page, Rachel; Thunders, Michelle
ABSTRACT: Online self-testing as part of the online learning environment (OLE) provides practice questions on key concepts with immediate feedback – in a 'no-risk' environment. OLE activity was analysed for 471 on-site and distance students enrolled in health science courses to determine total activity on the OLE and usage of online self-tests. The study also aimed to determine whether utilisation of self-tests differed by final grade, particularly between students who just pass (C grades and Restricted pass) and those who fail (D and E grades). Results indicated that on-site students were significantly more active on the OLE compared to distance students. However, these groups engaged similarly with self-tests and achieved a similar distribution of grades. A significant positive relationship was found between final grade achieved and percentage of self-tests attempted. This relationship was significant regardless of study status (on-site or distance), course studied or total activity logged. A more targeted analysis of C + R vs. D + E students showed that although these two groups were similar on overall usage of the OLE, C + R students utilised self-tests to a significantly greater extent. Recommendations from this study are that students (particularly those struggling to achieve academic success) should be directed towards online self-tests.